Proceedings of the 12th Koli Calling International Conference on Computing Education Research 2012
DOI: 10.1145/2401796.2401806
|View full text |Cite
|
Sign up to set email alerts
|

Automatic recognition of students' sorting algorithm implementations in a data structures and algorithms course

Abstract: Computing educators often rely on black-box analysis to assess students' work automatically and give feedback. This approach does not allow analyzing the quality of programs and checking if they implement the required algorithm. We introduce an instrument for recognizing and classifying algorithms (Aari ) in terms of white-box testing to identify authentic students' sorting algorithm implementations in a data structures and algorithms course. Aari uses machine learning techniques to classify new instances. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…Also in 2012, Taherkhani [38] revealed that AARI (e-assessment tool) was successful at recognizing the algorithms used by the students to perform sorting on integers for about 75% of the submissions.Further in 2014, Gaudencio [39] stated that instructors who manually graded the assignments also tend to agree more with the feedback provided by the tool in comparison to assessment provided by other instructors.…”
Section: Rq4 Is the Results Ibtained By E-iassessment Tiils Precise Amentioning
confidence: 99%
“…Also in 2012, Taherkhani [38] revealed that AARI (e-assessment tool) was successful at recognizing the algorithms used by the students to perform sorting on integers for about 75% of the submissions.Further in 2014, Gaudencio [39] stated that instructors who manually graded the assignments also tend to agree more with the feedback provided by the tool in comparison to assessment provided by other instructors.…”
Section: Rq4 Is the Results Ibtained By E-iassessment Tiils Precise Amentioning
confidence: 99%
“…Huang et al [1] use unit test results and AST edit-distance algorithms to identify clusters of submissions that could potentially receive the same custom feedback message. Taherkhani et al [4] identify which sorting algorithm a student implemented using supervised machine learning methods. Each solution is represented by statistics about language constructs, measures of complexity, and detected roles of variables.…”
Section: Related Workmentioning
confidence: 99%
“…Tackling problems with multiple solutions directly, Taherkhani et al [6] demonstrated the practicality of differentiating between multiple solutions, i.e., different sorting algorithms, in students' solutions to a particular engineering design problem using a supervised machine learning method.…”
Section: Related Workmentioning
confidence: 99%